Recurrent Clostridium difficile infection is associated with increased mortality. (February 2015) - Olsen, M.A.; Yan, Y.; Reske, K.A.; Zilberberg, M.D.; Dubberke, E.R.
Abstract: Clostridium difficile infections (CDI) are associated with decreased survival, and up to 30% of CDI patients may experience a recurrence. Data on the impact of recurrent CDI on mortality are scarce. The purpose of this study was to determine whether recurrent CDI was independently associated with decreased 6-month survival compared with patients with CDI who did not develop a recurrence. We performed a retrospective cohort study at an academic, urban, tertiary care hospital. Data were collected from the electronic medical record and chart review. CDI patients were followed for 180 days from the end of their index hospital discharge or end of index CDI antibiotic treatment, whichever was later, to determine mortality. Kaplan–Meier analysis was used to compare patient mortality by recurrent CDI status. Cox proportional hazards models were used to determine independent risk factors for death within 180 days. In all, 3958 patients aged ≥ 18 years who developed an initial CDI episode from 2003 to 2009, including 421 patients with recurrent CDI, were included in the study. Thirty-six per cent of persons with recurrent CDI died within 180 days, compared with 26% of persons without CDI recurrence (log-rank p <0.001). Recurrent CDI was associated with significantly higher hazards of death within 180 days, adjusting for demographics, comorbidities and medications received during the index CDI hospitalization (hazard ratio 1.33; 95% CI 1.12–1.58). Recurrent CDI is associated with significantly increased risk of death within 6 months after completion of their initial CDI treatment compared with CDI patients who do not develop a recurrence.